Review of Skin Cancer Detection Techniques Using Image Processing - Kaur, Balwinder (International Journal of Computer Sciences and Engineering, 2025)
One of the most dangerous diseases in the world today is cancer. The brain, lung, skin, liver, and other organs have various cancers. Finding cancer has proven to be difficult. Cancer has a good possibility of being cured if it is discovered early. The dangerous disease can only be cured in large part by detection. Feature extraction, segmentation, pre-processing, and classification are all steps in the detection process. Pre-processing is the stage where noise removal is possible. Segmentation can assist in dividing the image into different fields, feature extraction can assist in extracting features, and classification can assist in classifying and detecting the final cells. This paper provides a comprehensive overview of skin cancer and the role that digital image processing plays in its early identification. All research papers are taken from reputable journals that cover this topic.